Baby danced the polka - Beaumont, Karen; Plecas, Jennifer (New York : Dial Books for Young Readers, 2004)
It's nap time at the farm, but one un-sleepy baby has a different plan ... Baby wants to dance.
Keywords: Naps (Sleep) -- Fiction; Infants -- Fiction; Toy and movable books